CHARACTERISTICS OF RECEIVABLES WITHIN CURRENT ASSETS AND THEIR ROLE IN MANAGEMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the conditions of modernization of the economy, the issues of management of receivables in the economy of the Republic as an important component of current assets have not become the subject of scientific research. Perhaps the existence of receivables is considered as a negative situation in the financial management of economic entities.